Identification of natural product inhibitors against human Nicotinamide N-methyltransferase (hNNMT); An In-silico and In-vitro Approach - Harikrishna, A S; Kesavan, Venkitasamy (Synlett)
Human nicotinamide N-methyltransferase (hNNMT) plays a pivotal role in phase-II biotransformation. Notably, hNNMT's overexpression is common in various diseases, including metabolic disorders and various cancer types, which makes it as an attractive therapeutic target. The motivation of this research was to examine the potential inhibitory property of flavonoids against hNNMT. A panel of commercially available flavonoids were subjected to molecular docking to assess their binding affinity with hNNMT, followed by in vitro binding assays to validate inhibitory activity. hNNMT activity of these molecules were determined using spectrofluorimetry using Quinoline as the substrate. N-methylnicotinamide were used as positive controls. Quercetin and morin emerged as potent inhibitors of hNNMT activity by in vitro. Furthermore, comprehensive analyses encompassing physicochemical properties, pharmacokinetics, drug-likeness, and toxicity profiles were conducted for these compounds in silico. A 250 ns molecular dynamics simulation was performed on hNNMT complexes with Quercetin and Morin to substantiate their inhibitory potential. Morin exhibited the highest potency amidst the polyphenols screened, with an IC50 value of 14.97 ± 0.38 μM followed by Quercetin 29.95 ± 1.3 μM. This research highlights the significant inhibitory potential of Quercetin and Morin against hNNMT, and warrants incorporation of flavonoid scaffolds in designing inhibitors of NNMT.